Reflections on Baroque - Harbison, Robert, 1941- (Reaktion, 2000)
In this surprising reinterpretation of the Baroque, Robert Harbison offers new readings that stress its eccentric and tumultuous forms, in which a destablized sense of reality is often projected onto the viewer.